2019
DOI: 10.1098/rsos.190107
|View full text |Cite
|
Sign up to set email alerts
|

Long jumpers with and without a transtibial amputation have different three-dimensional centre of mass and joint take-off step kinematics

Abstract: Long jumpers with below the knee amputation (BKA) have achieved remarkable performances, yet the underlying biomechanics resulting in these jump distances are unknown. We measured three-dimensional motion and used multi-segment modelling to quantify and compare the centre of mass (COM) and joint kinematics of three long jumpers with BKA and seven non-amputee long jumpers during the take-off step of the long jump. Despite having the same jump distances, athletes with BKA, who used their affected leg for the tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, energy is stored (a portion of which is returned) in running-specific prostheses that may exceed that of a biological limb. In support, Funken et al [ 32 ] have shown that unilateral lower-limb amputees have a longer compression phase and a greater downward motion of the centre of mass, which would be effective in generating vertical impulse and storing and returning energy within the running-specific prostheses. An optimal running-specific prosthetic stiffness, one that maximizes the storage and return of energy while also maximizing the pivot that translates a portion of the horizontal velocity to vertical velocity at take-off [ 31 ] should be investigated.…”
Section: Standingmentioning
confidence: 99%
“…However, energy is stored (a portion of which is returned) in running-specific prostheses that may exceed that of a biological limb. In support, Funken et al [ 32 ] have shown that unilateral lower-limb amputees have a longer compression phase and a greater downward motion of the centre of mass, which would be effective in generating vertical impulse and storing and returning energy within the running-specific prostheses. An optimal running-specific prosthetic stiffness, one that maximizes the storage and return of energy while also maximizing the pivot that translates a portion of the horizontal velocity to vertical velocity at take-off [ 31 ] should be investigated.…”
Section: Standingmentioning
confidence: 99%
“…On the one hand, the reduced torque in the knee joint of the affected leg could indicate that this joint is likewise affected by the amputation. On the other hand, there are indicators that the conscious stiffening of the knee joint could be a strategy to make optimal use of the prosthesis [26,27]. At first glance, it seems appropriate in this context that the passive torque generated in the prosthetic ankle is almost twice as high as in the biological ankle.…”
Section: Validation and Analysis Of Joint Torquesmentioning
confidence: 99%
“…There aren't many athletes who haven't had an injury or surgery that places them with different "biological" abilities of what is originally natural. Similarly, there is no way to prove that a prosthesis is equivalent or not to a biological leg [22]. Therefore, "natural" is such an ambiguous term philosophically speaking that it should not be used by sports authorities as a rule.…”
Section: What Is Natural In the Era Of Technologization In Sport?mentioning
confidence: 99%